Forestry and Bee-keeping in Kulu - Singh, D. P. (Indian Forester, 1951)
Kulu has been an important source of honey, but due to excessive grazing, browsing and burning of forest vegetation which forms the bee pasture, the production has suffered a serious set-back in recent years, so much so that the bee-keepers are now getting anxious about the industry. Afforestation in Kulu, is to the bees what grow-more-food is to the people in general. The relation between forestry and bee-keeping is very intimate and incidentally in Kulu, the species useful as bee-flora are also of great utility for general needs and soil stabilization. We must, therefore, do our best to protect, extend and improve the bee-flora before it gets too late.